Mathematical modelling of vehicle assembly line for throughput enhancement. (2016) - Rane, Arun Bhiva; Sunnapwar, Vivek K.; Khot, S.M.; Vulavala, Ramesh
The objective of this work is to improve the performance of vehicle assembly line by developing suitable mathematical relations between various influencing parameters affecting throughput. This work also systematically identifies and describes different approaches adopted by various research scholars through systematic review of peer-reviewed papers from reputable journals. There are several uncertainties in manufacturing environments. Here, mathematical models are developed to consider the impact of important influencing factors like equipment failure, short supply of material, absenteeism, set-up, material handling, rejection and fatigue on throughput. Then, inter-relationships are established between these parameters. Relationships between these parameters and their corresponding cost are also developed. Relationships are established scientifically using regression modelling, MATLAB, Minitab, Excel, Arena and discussions with domain experts. These are validated with real world data. Practitioners may use these models to predict and control uncertainty. Further, within a given cost constraint and using lean techniques, cycle time may be reduced.